2009
DOI: 10.1007/s12031-009-9237-0
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Receptors, Amyloid-β, and Synaptic Failure in Alzheimer’s Disease

Abstract: Dysfunctional cholinergic transmission is thought to underlie, at least in part, memory impairment and cognitive deficits in Alzheimer's disease (AD). However, it is still unclear whether this is a consequence of the loss of cholinergic neurons and elimination of nicotinic acetycholine receptors (nAChRs) in AD brain or of a direct impact of molecular interactions of the amyloid-beta (Abeta) peptide with nAChRs, leading to dysregulation of receptor function. This review examines recent progress in our understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 91 publications
(112 reference statements)
1
45
0
2
Order By: Relevance
“…In AD, synaptic dysfunction and failure are closely related to the clinical symptoms [22]. In this study, we investigated a role for neuritin in the cellular and cognitive features of AD.…”
Section: Discussionmentioning
confidence: 99%
“…In AD, synaptic dysfunction and failure are closely related to the clinical symptoms [22]. In this study, we investigated a role for neuritin in the cellular and cognitive features of AD.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors are localized throughout the cortex, hippocampus, amygdala, hypothalamus, striatum, and other regions involved in these cognitive processes [13]. Because decreased levels of these receptors have been found in AD brains [58], this reduction is considered to explain, at least in part, the cognitive deficits in AD.…”
Section: Nicotinic Acetylcholine Receptors (Nachrs) As a Therapeutic mentioning
confidence: 99%
“…These receptors are localized throughout the cortex, hippocampus, amygdala, hypothalamus, striatum, and other regions involved in these cognitive processes [13]. Because decreased levels of these receptors have been found in AD brains [58], this reduction is considered to explain, at least in part, the cognitive deficits in AD.The α7 receptors are very important for mediating sensory gating, attention and learning, and memory, making them an ideal target to improve these cognitive functions. However, these receptors are susceptible to agonist-induced desensitization, a characteristic that complicates the use of agonists as therapeutic agents.…”
mentioning
confidence: 99%
“…The predominant clinical symptoms early associated with Alzheimer’s disease (AD) include a deficiency in memory capabilities and these deficits are linked to a selective impairment of cholinergic function (Buckingham et al, 2009; Jürgensen and Ferreira, 2010). It has been reported that a significant decrease in the number of α4 nicotinic acetylcholine receptors (nAChRs) is one of the earliest events in the pathogenesis of AD (Burghaus et al, 2000) even preceding cholinergic neuronal degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Aβ can interact in different ways with the nAChRs depending on the receptor subtype as well as on Aβ peptide concentration or type of preparation (monomers versus oligomers) or incubation times (Jürgensen and Ferreira, 2010). It seems that Aβ might bind with high affinity (picomolar range) to α7 receptors (Wang et al, 2000; Khan et al, 2010; Tong et al, 2011), although this remains controversial (Small et al, 2007), and produces both stimulatory (Dougherty et al, 2003; Puzzo et al, 2008; Mura et al, 2012) and inhibitory effects (Liu et al, 2001; Pettit et al, 2001) suggesting a distinct regulatory role depending on the receptor location (Tong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%